Pengaruh Arus Dan Tegangan Terhadap Prototype PLTS Berbasis Mikrokontroller Arduino Uno - Makruf, Abdul; Rahmadhani, Rizal; Ningsih, Pratika Sulistya; Jayaditama, Wiki; Rani, Nur; Ningsih, Alham (Teknik Elektro Universitas Lancang Kuning, 2022)
This factory uses solar cells as the main source of electricity generation. The aim is to design and build an acquisition system that can read currents, voltages, temperatures, and power in solar cells, measure the performance of current, voltage, temperature, and power data acquisition systems generated by solar cells. The PV efficiency value is 9.85%, with a FF value of 0.776 which indicates that the FF value is not low. Also achieved a power efficiency value of 9.82% which is not far from the value of PV efficiency. However, this value is still far from 100% due to loss or loss of power or condition which is one of the factors that cause losses resulting in loss of some energy output. From the duration of 1 and 2 hours of data drying on PV using a load, it appears that V and I are lower than 1 and 2 hours of data drying without using a load, because V and I output PV is not absorbed by the load.